Study of the effect of different concentrations of IBA (Indol Butyric Acid) in reducing the number of Cupressus macrocarpa cuttings. L. Non-rooted callus - غرير لؤي; حسن علاء الدين; أمين صالح (Latakia University Journal -Biological Sciences Series, 2023)
This research aims to study of stem’s propagation. Cuttings the Cupresus mecrocarba L. b by different concentration of rotting hormone IBA (1000ppm, 2000ppm, 3000ppm, 0 control). This research was conducted during the year 2020, in the greenhouse, Tishreen Agriculture Center of the Directorate of Agriculture and Agrarian Reform in Lattakia. The experiment was carried out using randomized complete sectors with four replications, and the number of cuttings in one treatment was 100 heads. The results showed that hormone IBA had a clear effect on rooting in terms of the percentage of rooted cuttings. The number of roots and their growing lengths on a single cutting. The results also showed that the hormone with a concentration of 3000ppm was superior in terms of the percentage of rooted cuttings. The total lengths of the roots and the average length of the roots on one cutting, with a concentration of 2000ppm and a concentration of 1000ppm.